2012
DOI: 10.1128/jvi.01517-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Duck Enteritis Virus Strains

Abstract: cThe icosahedral virion of duck enteritis virus (DEV) is roughly spherical and approximately 150 nm in diameter. Here, we describe the genomic features of DEV CHv together with a draft genome sequence and its annotation, highlighting the homogeneity and heterogeneity of this genome in comparison with its reference genomes. Duck enteritis virus (DEV) is an epornitic agent. It causes considerable economic losses to the commercial duck industry and poses a continuous threat to wild and migratory waterfowl populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 30 publications
(2 reference statements)
0
41
0
Order By: Relevance
“…A significant difference may also be seen in arrangement of inverted and directly repeated sequences (Hayward et al 1975;Wadsworth et al 1976). Partial or complete genomic sequences of DEVs are rapidly accumulating and its analyses demonstrated that, although similar to other herpes viruses, the DEV genome also varies Wang et al 2011;Wu et al 2012a;Wu et al 2012b;Yang et al 2013). The Chinese DEV is a wild type virulent strain of DEV (Gao et al 2015).…”
Section: Etiologymentioning
confidence: 99%
“…A significant difference may also be seen in arrangement of inverted and directly repeated sequences (Hayward et al 1975;Wadsworth et al 1976). Partial or complete genomic sequences of DEVs are rapidly accumulating and its analyses demonstrated that, although similar to other herpes viruses, the DEV genome also varies Wang et al 2011;Wu et al 2012a;Wu et al 2012b;Yang et al 2013). The Chinese DEV is a wild type virulent strain of DEV (Gao et al 2015).…”
Section: Etiologymentioning
confidence: 99%
“…DEV is a linear, double-stranded DNA virus, the genome size of which is approximately 158–162 kb [36]. The entire genome of DEV is composed of a unique long (UL), a unique short (US) and two inverted repeated sequences (IRS and TRS) [6].…”
Section: Findingmentioning
confidence: 99%
“…There is very high identity between the 63rd-passage strain and DEV strain VAC (5), with a difference of only 44 single-nucleotide polymorphisms. Compared with the virulent DEV strains CHv (6, 7) and 2085 (8), the 63rd-passage strain had a 3,513-bp deletion and a 2,497-bp deletion, respectively, after nucleotide 2715, causing a frameshift in long ORF 11 (LORF11). Additionally, there was a 528-bp deletion that caused the deletion of 176 amino acids in the frame of unique long region 2 (UL2).…”
Section: Genome Announcementmentioning
confidence: 99%